Bird of paradise - Vidor, King, 1894-1982; Del Rio, Dolores, 1905-1983; McCrea, Joel, 1905-1990; Halliday, John, 1880-1947; Gallagher, Skeets, 1890-1955; Roach, Bert, 1891-1971; Selznick, David O., 1902-1965; Root, Wells; Tuchock, Wanda; Praskins, Leonard; Tully, Richard Walton, 1877-1945.; Radio Pictures; et al. ([Los Angeles, CA] : Radio Pictures, 1932)
A handsome South Seas soldier of fortune falls in love with the daughter of a Polynesian native chieftain. Alas, their idyllic romance is destined to come to a sudden and violent end: tribal custom decrees that she is to be sacrificed to the local volcano. After initial resistance, the heroine nobly resigns herself to her fate, realizing that there is no place for her in her white lover's civilization.
Originally produced in the United States as a motion picture in 1932.
Movie distributed by Cinetel for Digitalia Film Library.
Dolores del Rio, Joel McCrea, John Halliday, Richard "Skeets" Gallagher, Bert Roach.
Photographed by Clyde de Vinna, Edward Cronjager, Lucien Andriot; music by Max Steiner; editor, Archie F. Marshek.
Based on: Bird of paradise / Richard Walton Tully.
In Spanish.
Keywords: Human sacrifice -- Drama; Oceania -- Drama; Man-woman relationships -- Drama; Romance films; Internet videos; Feature films; Fiction films; Streaming video